2021
DOI: 10.3389/fonc.2021.705331
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of NLRP3 Inflammasome and TLR4 Expression in Breast Cancer Patients

Abstract: Inflammasome complexes play a pivotal role in different cancer types. NOD-like receptor protein 3 (NLRP3) inflammasome is one of the most well-studied inflammasomes. Activation of the NLRP3 inflammasome induces abnormal secretion of soluble cytokines, generating advantageous inflammatory surroundings that support tumor growth. The expression levels of the NLRP3, PYCARD and TLR4 were determined by immunohistochemistry in a cohort of primary invasive breast carcinomas (BCs). We observed different NLRP3 and PYCAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 53 publications
2
13
0
Order By: Relevance
“…Our recent data demonstrated a higher NLRP3 and PYCARD expression in the tumor compartment with respect to the non-tumor areas in a BC cohort [14]. Here, we confirm the high NLRP3 and PYCARD expression in tumor samples (50% and 31%, respectively) as well as an overexpression of CyclinD1 and MYC, (48% and 32%, respectively).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Our recent data demonstrated a higher NLRP3 and PYCARD expression in the tumor compartment with respect to the non-tumor areas in a BC cohort [14]. Here, we confirm the high NLRP3 and PYCARD expression in tumor samples (50% and 31%, respectively) as well as an overexpression of CyclinD1 and MYC, (48% and 32%, respectively).…”
Section: Discussionsupporting
confidence: 87%
“…Our previous study demonstrated the overexpression of NLRP3 in the tumor compartment compared to the non-tumor area in primary invasive BCs and its impact on disease free survival (DFS). In fact, high NLRP3 expression was associated with a worst DFS in this BC cohort [14]. Inflammasome crosses different pathways involved in cancer progression, including the Wnt/β-catenin/CyclinD1 signaling.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…Subsequently, we predicted the downstream targets of miR-603 using the miRDB database. 6 genes (NFIB [ 27 ], ZEB2 [ 28 ], TLR4 [ 29 ], KDM7A [ 30 ], LASP1 [ 31 ], and KIF2A [ 32 ]) related to BC were selected as candidate targets for further analysis among all predicted target genes. Moreover, only KIF2A was repressed in both miR-603-overexpressing HCC70 and MDA-MB-231 cells, so KIF2A was selected for subsequent investigation (Additional file 3 : Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The reduced expression of NLRP3 in colorectal cancer (CRC) tissue holds a positive predictive value [93]. Likewise, the upregulation of NLRP3 expression in breast cancer heralds a poorer five-year survival rate [94]. The capability of the NLRP3 inflammasome to promote an immune response provides the potential to predict the response to immunotherapy.…”
Section: The Nlrp3 As Biomarkermentioning
confidence: 99%